Game over: Asian Americans and Video Game Representation - Phi, Thien-bao Thuc (Transformative Works and Cultures, 2009)
Even video games by Asian creators tend to depict primarily white characters or reference Asian stereotypes such as kung fu fighters or yakuza thugs. Games depicting the Vietnam war are particularly troubling for Asian players expected to identify with white characters. As the game industry continues to expand, its representation of Asians and Asian Americans must change.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé